Analysis of SGPT and SGOT on Rats Induced By Isoniazid to Determine Dose and Hepatoprotective Characteristic of Unripe Pineapple Juice (Ananas comosus L. Merr) - Lestari Rahayu; Novi Yantih; Yoana Supomo (Fakultas Farmasi Universitas Pancasila, 2018)
As a consequence of Isoniazid (INH) consumption in longterm is the damage on the liver cells which is detected in high level of SGPT and SGOT in blood. Unripe pineapple fruits contained higher level of phenolic acid and flavonoids compounds than the ripe pineapple fruits, and as a result the unripe pineapple fruits juice has higher hepatoprotective potency than ripe pineapple fruits juice. The hepatoprotective activity of unripe pineapple fruits juice was determined by measuring the SGPT and SGOT level on rat blood. There were prepared 24 rats, divided into 6 groups, i.e. normal control group, positive control group, negative control group, and 3 test goups that were induced by INH and each was given the unripe pineapple fruits juice at 1 hour before and 1 hour after INH induction, with the dose of 2 mL and 4 mL. Treatment was conducted in 14 days, consecutively. To each of the rat groups, blood was taken out through the eye orbital sinus, i.e. on the first day, on the hour-0 and hour-3, and then the SGPT and SGOT level were measured. Later on, blood were taken out on the day-4, day-7, and day-14. On the rat blood that were taken out, were analyzed descriptively and statistically to determined the optimum dose and the time of the unripe pineapple fruits juice feeding in related with a hepatoprotective potency. Result showed that feeding of the unripe pineapple fruit juice 1 hour after INH induction with the dose of 2 mL during 14 days has the best hepatoprotective activity.